Organoleptic Acceptability and Nutritional Value of Yogurt Corn Pudding as an Alternative Snack for Toddlers - Hadju, Vidya; Aulia, Ulfa; Ahmad, Zul Fikar (Poltekkes Kemenkes Palu, 2025)
Background: Improving people’s nutritional status is the second indicator of the Sustainable Development Goals (SDGs), which are realized by working towards ending hunger, achieving food security and good nutrition, and promoting sustainable agriculture. Safe and healthy snacks​ for toddler that fulfill nutrition adequacy are very important in supporting the growth and development of toddlers. Snacks in the form of yoghurt corn pudding are expected to be an alternative to supplementary feeding for underweight toddlers. This study aimed to analyze the nutritional content and acceptability of yogurt corn pudding. Methods: This research is an experimental study with a design using a Randomized Block Design (RBD) of 1 factor and 3 levels of treatment, with 3 repetitions. This formulation of corn and yogurt used were F1 (80% corn and 20% yogurt); F2 (60% corn, and 40% yogurt); F3 (50% corn, and 50% yogurt). Organoleptic test included colour, aroma, taste and texture using hedonic scale test form to 35 moderately trained panelists. Proximate nutrient content analysis was conducted in the Food Technology laboratory of Gorontalo State University. Data analysis of organoleptic results using Kruskal-Wallis Test. Results: Statistical test results show that there were significant differences (p< 0.05) for all parameters in the hedonic test. Yogurt corn pudding formula 1 was the best formula and acceptable to the panellists. The proximate nutrient content of the yogurt corn pudding was carbohydrates 22.85%, fat 1.43%, protein 7.85%, water content 66.40 %, ash content 1.47%, total sugar 28.57%, calcium 25.03%, energy 136.03 kcal. Conclusion: The nutritional content of pudding formula 1 that meets 10% of the toddler Nutrition Adequacy Rate is carbohydrates, protein, energy. Those that did not meet the 10% of the toddler Nutrition Adequacy Rate were fat and calcium. The sugar content is quite low. Corn Yogurt Pudding can be used as an alternative supplementary food for toddlers